Use of Nitrification Inhibitor DMPP to Improve Nitrogen Uptake Efficiency in Citrus Trees - Martínez-Alcántara, Belén; Quinones, Ana; Polo, Carolina; Primo-Millo, Eduardo; Legaz, Francisco (Canadian Center of Science and Education, 2020)
In citrus orchards, nitrogen uptake efficiency (NUE) is between 40 to 60% where any excess of nitrate is subjected to leaching below the rooting zone. The compound, 3,4-dimethylpyrazole phosphate (DMPP) inhibits the nitrification process in soil thus reducing/delaying nitrate leaching. The objective of this study was to evaluate the performance of DMPP added to ammonium sulphate (AS+DMPP), compared to ammonium sulphate (AS) and calcium-potassium nitrate (CPN), in fertigation of bearing orange trees grown outdoors in drainage lysimeters. Fertilizers were 15N-labeled to trace N through soil-plant-drainage system. Soil was sampled monthly from April to December and trees were destructively harvested in December. In trees fertilized with AS+DMPP, increased biomass was observed with a more profuse development of root system and higher fruit yield. Fertilizer 15N uptake significantly increased with DMPP addition. In AS+DMPP amended soils, increased values of -15N and lower -N concentrations were recorded from April to June as evidence of the inhibitory effect of DMPP on the nitrification process during this period. In CPN and AS fertilized soils, 15N losses in drainage solutions represented 9-10% of the fertilizer supplied whereas less than 3% was leached when DMPP was added. At the end of the cycle, highest NUE was recorded in the AS+DMPP treatment (69%), while CPN and AS had lower values (61% and 54%, respectively). Therefore, the use of DMPP enables a more efficient utilization of the fertilizer-N in citrus trees, minimizing the risk of nitrate-N pollution in groundwater. However, DMPP supply should be considered during spring fertilization, since high temperatures of summer months significantly reduced its activity.